World Wide Video Festival 1989. - Kijkhuis, Den Haag; World Wide Video Festival, Den Haag (Den Haag : Kijkhuis, 1989)
Allard, Roland ; Andrié, Luc ; Corminboeuf, Denis ; Atlas, Charles ; Aubier, Pascal ; Augustijns, Annemie ; Balser, Michael ; Fabo, Andy ; Bearden, Victoria ; Beaugrand, Cathérine ; Beban, Breda ; Horvatic, Hrovoje ; Bergese, Micha ; Snow, George ; Bianconi, Lorédana ; Bourges, Alain ; etc.
World Wide Video Festival 1989, Kijkhuis, Den Haag, 1989
Nederlands & Engels
boek